Neurological Spectrum of COVID-19: A Practical Review - Mehmet Akif Topçuoğlu; Şerefnur Öztürk (Türk Nöroloji Dergisi, 2021)
Coronavirus disease-2019 (COVID-19) can be associated with wide-range neurologic symptoms and complications. Parainfectious manifestations that are seen during the active infection period include stroke, olfactory and taste disturbance, encephalopathy, encephalitis, neuropathies, and myopathies. The main postinfectious complications are acute disseminated encephalomyelitis, transverse myelitis, Guillain-Barré syndrome, cognitive disorders, and sleep disorders. COVID-19 commonly causes neurological mid-to-long-term disability. The disease prognosis can be improved with sufficient knowledge, prompt recognition, and effective management of neurological complications.